Analysis of The Student's Ability to Interconnect Macro-Submicro-Symbolic Representation on Electrolyte Solution Concept - Langitasari, Indah; Robandi, Babang (EduChemia: Jurnal Kimia dan Pendidikan, 2023)
A comprehensive understanding of chemistry requires thinking using three levels of interconnected representation: macroscopic, submicroscopic, and symbolic. Electrolyte solutions are one of the concepts in chemistry that need to involve the interconnection of the three levels of chemical representation in studying them. This study aims to analyze the students' ability to interconnect the three levels of chemical representation in the electrolyte solutions concept. This research used a descriptive quantitative research design. The research instrument used The Multiple Representation of Electrolyte Test (MRET). The research data were analyzed descriptively based on the students' answer patterns. The results showed that the student's ability to interconnect the three levels of chemical representation in the electrolyte solutions concept is low. Students are only able to make interconnections between macroscopic and symbolic levels.